2019
DOI: 10.1175/jhm-d-18-0035.1
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic Forcing on Interannual Variability of Sahel Heavy and Moderate Daily Rainfall

Abstract: This article analyzes SST remote forcing on the interannual variability of Sahel summer (June–September) moderate (below 75th percentile) and heavy (above 75th percentile) daily precipitation events during the period 1981–2016. Evidence is given that interannual variability of these events is markedly different. The occurrence of moderate daily rainfall events appears to be enhanced by positive SST anomalies over the tropical North Atlantic and Mediterranean, which act to increase low-level moisture advection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 47 publications
6
22
1
Order By: Relevance
“…For the Mediterranean (Figures 1-3 and Figure 6), evidence was given that statistical prediction of heavy daily precipitation based on SSTs is possible up to one month in advance (predicting August precipitation in July) over a widespread area of the Sahel. These results are consistent with previous studies, as a warmer Mediterranean is known to foster humidity supply and convergence over vast Sahel areas during boreal summer [15,21,34,37]. On the contrary, colder SSTs over the Mediterranean are generally linked with a drier Sahel.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For the Mediterranean (Figures 1-3 and Figure 6), evidence was given that statistical prediction of heavy daily precipitation based on SSTs is possible up to one month in advance (predicting August precipitation in July) over a widespread area of the Sahel. These results are consistent with previous studies, as a warmer Mediterranean is known to foster humidity supply and convergence over vast Sahel areas during boreal summer [15,21,34,37]. On the contrary, colder SSTs over the Mediterranean are generally linked with a drier Sahel.…”
Section: Discussionsupporting
confidence: 93%
“…In this paper, the novel Sea Surface temperature based Statistical Seasonal ForeCAST model (S4CAST; [36]) was utilized to exhaustively analyze the timing and spatial structure of the relation between Sahel heavy/extreme (75/95th percentile) daily precipitation events and skillful oceanic predictors identified in previous work: El Niño Southern Oscillation (ENSO) and the Mediterranean Sea [37]. To this aim, the NOAA Extended Reconstructed Sea Surface Temperature (SST) data set (ERSST), the Climate Hazards Group Infrared Precipitation with Station Data (CHIRPS) and the European Center for Medium-Range Weather Forecasts (ECMWF) ERA-Interim reanalysis were utilized for the period of 1982-2015.…”
Section: Discussionmentioning
confidence: 99%
“…The ERA5 dataset, a reanalysis product from the European Centre for Medium-Range Weather Forecasts (ECMWF, Hersbach et al, 2020), is used as a reference to evaluate the performance of the CMIP6 models in simulating the surface and atmospheric fields under present-day conditions. ERA5 has replaced ERA-Interim (Dee et al, 2011) that has been widely used to study the characteristics of the West African climate (Manzanas et al, 2014;Lavaysse et al, 2015;Kebe et al, 2016;Raj et al, 2018;Maranan et al, 2018;Diakhaté et al, 2019Diakhaté et al, , 2020Wainwright et al, 2019). ERA5 for instance shows an improvement of the rainfall representation over Burkina Faso (Tall et al, 2019), which is a part of the Sahelian region.…”
Section: Methodsmentioning
confidence: 99%
“…The difference of the wind divergence between 200 hPa and 850 hPa levels (DIV200/850) is used to evaluate the direction and intensity of the vertical air motion (Gómara et al, 2017;Diakhaté et al, 2019). Positive values of this difference (upper level minus low level) means that there is a low level convergence of the wind, an ascent and a divergence at high level.…”
Section: Methodsmentioning
confidence: 99%
“…These studies have demonstrated the important role of sea surface temperatures (SSTs) with respect to the last drought over the Sahel (Folland et al,1986;Mohino et al, 2011;Rodríguez-Fonseca et al, 2015). Interannual variation of rainfall is also related to the phase of El Niño-Southern Oscillation (ENSO; Janicot et al,1996;Diakhaté et al, 2019;Hart et al, 2019). However, state-of-the-art climate models still struggle to reproduce precipitation variability and trends in West Africa through the historical period, which is mainly due to their low skill in simulating the observed SST teleconnections (Rowell, 2013).…”
Section: Introductionmentioning
confidence: 99%